Genetic study on post-harvest root deterioration in cassava - Kawano, K; Rojanaridpiched, C (1983)
Postharvest root deterioration or vascular streaking of cassava clones (accessions and breeding lines) was evaluated with harvests at different ages (8 and 12 mo.), seasons (beginning and end of wet season), and locations (CIAT-Palmira, Carimagua, and Caribia in Colombia) to assess the effect of environmental factors on cassava genotypes. Vascular streaking was sensitive to any of these environmental factors. Genotype x location interaction was highly significant suggesting that final cv. selection should be carried out in each location. Genetic analysis carried out in one location suggested that inheritance of vascular streaking was, at least partly, controlled by additive factors and was quantitative rather than qualitative. Narrow sense heritability of 0.64 was obtained. Vascular streaking was highly and significantly correlated with root DM content in all the trials conducted during 7 yr. Since free recombination between resistance to vascular streaking and high root DM content may not be possible, the most acceptable balance between these 2 traits should be defined according to the use of product and edaphoclimatic condition of production area prior toselection program. (AS)